Validation of sanitation of food service establishments in UPV , Miag-ao campus - Ducusin , Alexander Malicana (2003.)
The sanitary condition of food service establishments in UPV, Miag-ao campus was evaluated.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Sanitation; Food service